Proteasome inhibitors activate autophagy as a cytoprotective response in human prostate cancer cells - Zhu, Keyi (2009)
The ubiquitin-proteasome and lysosome-autophagy pathways are the two major intracellular protein degradation systems that work cooperatively to maintain homeostasis. Proteasome inhibitors (PIs) have clinical activity in hematological tumors, and inhibitors of autophagy are also being evaluated as potential antitumor therapies. In the current study we found that chemical proteasome inhibitors and siRNA-mediated knockdown of the proteasome's enzymatic subunits promoted autophagosome formation, stimulated autophagic flux, and upregulated expression of the autophagy specific genes (ATGs) (ATG5 and ATG7) in some human prostate cancer cells and immortalized mouse embryonic fibroblasts (MEFs). Upregulation of ATG5 and ATG7 only occurred in cells displaying PIs-induced phosphorylation of the eukaryotic translation initiation factor 2alpha (eIF2α), an important component of the unfolded protein responses. Furthermore, PIs did not induce autophagy or upregulate ATG5 in MEFs expressing a phosphorylation-deficient mutant form of eIF2α. Combined inhibition of autophagy and the proteasome induced an accumulation of intracellular protein aggregates reminiscent of neuronal inclusion bodies and caused more cancer cell death than blocking either degradation pathway alone. Overall, our data demonstrate that proteasome inhibition activates autophagy via a phospho-eIF2α-dependent mechanism to eliminate protein aggregates and alleviate proteotoxic stress.